Employment for People with Disability: Some Findings on the Policy and Implementation - Wahab, Harlida Abdul; Ayub, Zainal Amin; Arshad, Rozita (International Review of Management and Marketing, 2017)
Employment for people with disability (PWD) is a challenging issue. It is common for PWD to experiencing severe economic deprivation and social disadvantages. To acknowledge and ensure their employment right, almost all the governments of all countries in the world has managed to bring in policies relating to PWD. These have been reflected in the enactments, laws, regulations, schemes, and also institutions established for the development and wellbeing of PWD. Consequently, there have been positive changes in the society towards PWD. This paper discusses the employment of PWD in Malaysia by looking at the policies and their implementation. Using a qualitative approach, a number of respondents who deal with the policies and PWD were interviewed to understand the issues, problems and experiences of PWD. The study found that the government has shown a great effort by introducing various policies and laws, holding programmes as well as proposing initiatives to support rights and enhance life of PWD in Malaysia. Yet, when it comes to employment, further improvements are expected particularly in terms of the implementation together with the understanding and cooperation from the employers. Keywords: People with Disability, Employment, Policy, Implementation JEL Classifications: J71, J78, K31